The fatty acid profiles in M. longissimus dorsi and M. semimembranosus of short-haired and long-haired crossbred sheep meat - Pattraphorn Patthararangsarith; Kunya Tuntivisoottikul (My University, 2018)
This study was conducted to investigate the effects of crossbred groups and anatomical muscle positions on the chemical composition and fatty acid profiles in the loin ( M. longissimus dorsi ) and chump ( M. semimembranosus ) muscles of the short-haired and long-haired crossbred sheep. Five sheep per group with the 25 kg initial body weight were fed with 2 kg/d TMR and free choice grass ( Brachiaria mutica ), and those were raised 84 days. After slaughter, loin and chump were used to examine the chemical composition and fatty acid profiles. The results showed that the loin from the short-haired and long-haired crossbreds had Palmitic acid at the highest level among the other saturated fatty acid (SFA), whereas this fatty acid was not detected in the chump. However, the highest SFA in the chump of both crossbreds was the Stearic acid. Furthermore, the fatty acids in both groups were detected in the chump more than in the loin. There was found that the nutritional values were not affected by sheep crossbred groups (P>0.05). The loin and chump had affected the percentage of crude protein (P<0.01), the amount of Lauric Acid (C12:0), and the total fatty acids (P<0.01). Interaction factor between the crossbred groups and the anatomical muscle positions was unaffected all the traits studied (P>0.05).
Keywords: Loin; Stearic acid; Saturated fatty acid; Longissimus dorsi; Meat and Animal Product Quality